ANALISIS PENJADWALAN WAKTU MENGGUNAKAN METODE CPM DAN PERT PADA PEMBANGUNAN GUDANG DEXA MEDICA PALEMBANG - Lega Reskita Lubis; Zuul Fitriana Umari; Kristi Kristi; Akhirini Akhirini (LATERAL: Jurnal Teknik Sipil, 2023)
The project is a series of sensitive work mechanisms because each aspect of the project is interconnected with each other. The purpose of this research is to determine the planned duration, critical path activities, and probability in the implementation of the Dexa Medica warehouse construction project in Palembang. Primary data used for estimation of work time, while secondary data used time schedules (S-curve) and work plan drawings. The methods used are the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT). The planned project completion duration using the CPM calculation method is 39 weeks. The activities known to be on the critical path are preparation, earthworks and others on the 1st floor, concrete work on the 1st floor, architectural work on the 1st floor, site development, and genset room work. The planned project completion duration using the PERT calculation method is 40.2 weeks. The probability (Probabiliti) with the PERT method is found to be 0.7324, meaning that there is a 73.24% probability that the project will be completed within 41 weeks.